2007
DOI: 10.1021/es0700303
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile Biomarkers of Metal Contamination in a Sentinel Terrestrial Species Are Applicable Across Multiple Sites

Abstract: In this study, we addressed the question of whether an omic approach could genuinely be useful for biomarker profile analysis across different field sites with different physicochemical characteristics. We collected earthworms (Lumbricus rubellus) from seven sites with very different levels of metal contamination and prevailing soil type and analyzed tissue extracts by 1H nuclear magnetic resonance spectroscopy. Pattern recognition analysis of the data showed that both site- and contaminant-specific effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 42 publications
(37 reference statements)
2
68
0
Order By: Relevance
“…HEFS was identified in diverse earthworm species including Eisenia veneta, Lumbricus rubellus, Aporrectodea caliginosa and E. fetida [27,28,42,43]. Although the function of HEFS in earthworms was not fully understood, it was suggested that HEFS might play a role in membrane stabilization due to its amphiphilic property [27,28].…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…HEFS was identified in diverse earthworm species including Eisenia veneta, Lumbricus rubellus, Aporrectodea caliginosa and E. fetida [27,28,42,43]. Although the function of HEFS in earthworms was not fully understood, it was suggested that HEFS might play a role in membrane stabilization due to its amphiphilic property [27,28].…”
Section: 2mentioning
confidence: 99%
“…Although the function of HEFS in earthworms was not fully understood, it was suggested that HEFS might play a role in membrane stabilization due to its amphiphilic property [27,28]. The decrease of HEFS could mean that BDE 47 induced disturbance in membrane stabilization in E. fetida at concentrations ranged from 0.1 to 100 μg/L.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous observation of possible bimodal distributions of metabolites in L. rubellus was not based on enough individuals to confirm the existence of sub-populations [23]. Metabolomics is often used to study the relationship of genotype to phenotype [24].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics are used as a key instrument to understand the environmental responses in plants (Bundy et al, 2007). Recently, they are being used as key instrument to study biogenic volatile compounds produced by various plant species (Lijima, 2014).…”
Section: Plant Metabolomicsmentioning
confidence: 99%